A resource environment for research on multi-disease resistance - Wissocq, N.M.; Ngamuna, S.; D'Ieteren, G.D.M. (OAU/STRC, 2001)
The evaluation of the interactions between trypanosome risk, disease control methods and the productivity require high consideration so that sustainable strategies that are best adaptable to the specific needs, constraints and opportunities of the production systems are worked out. There is no unique solution for all the production systems, all the ecological zones or all the types of markets. Trypanosomosis may be the single most important animal disease in subSaharan Africa. However, other animal health constraints limit agriculture and livestock production in the humid and sub-humid zones of the continent. Among the most important are dermatophilosis, tick infections and tick-borne diseases, and gastrointestinal parasitosis. The interactions between these diseases and their combined effects on animal productivity are crucial to assess host capabilities to cope with or to resist them, particularly as traits estimating resistance to parasites and diseases are increasingly being exploited within integrated health management strategies. The posters Reports on the specifics of an eco-system in which research on interactions among diseases and on the exploitation of multi-disease resistance traits can be optimally carried out. It is concluded that the specific climate, vegetation, land-use, prevalence and risk of endemic tropical diseases, animal husbandry and methods or animal health management practiced in this N'Dama cattle population provides an excellent environment for individual animals to express their respective levels of disease resistance to the most economically important animal parasites/diseases.